Identification of NCAN as a candidate gene for developmental dyslexia - Einarsdottir E (NATURE PUBLISHING GROUP, 2022)
A whole-genome linkage analysis in a Finnish pedigree of eight cases with developmental dyslexia (DD) revealed several regions shared by the affected individuals. Analysis of coding variants from two affected individuals identified rs146011974G >A (Ala1039Thr), a rare variant within the NCAN gene co-segregating with DD in the pedigree. This variant prompted us to consider this gene as a putative candidate for DD. The RNA expression pattern of the NCAN gene in human tissues was highly correlated (R > 0.8) with that of the previously suggested DD susceptibility genes KIAA0319, CTNND2, CNTNAP2 and GRIN2B. We investigated the association of common variation in NCAN to brain structures in two data sets: young adults (Brainchild study, Sweden) and infants (FinnBrain study, Finland). In young adults, we found associations between a common genetic variant in NCAN, rs1064395, and white matter volume in the left and right temporoparietal as well as the left inferior frontal brain regions. In infants, this same variant was found to be associated with cingulate and prefrontal grey matter volumes. Our results suggest NCAN as a new candidate gene for DD and indicate that NCAN variants affect brain structure.